Fatigue and Fracture Mechanics: 32nd Volume 2002
DOI: 10.1520/stp10592s
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Analyses of Crack-Tip-Opening Angles and δ5-Resistance Curves for 2024-T351 Aluminum Alloy

Abstract: The objective of this paper was to investigate the fracture behavior of compact and middle-crack tension specimens made of 6.35 mm thick 2024-T351 aluminum alloy. Tests were conducted on compact tension, C(T), specimens ranging in width from 51 to 152 mm and on middle-crack tension, M(T), specimens ranging in width from 76 to 1016 mm. Most of the M(T) specimens were allowed to buckle during the fracture tests. Three-dimensional, elastic-plastic, finite-element analyses (FEA) using the WARP3D code with straight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Later, the nonconstant CTOA values were traced to inappropriate state‐of‐stress (or constraint) assumptions in the crack‐front region and severe crack tunnelling in thin‐sheet materials . More recently, the CTOA fracture criterion has been used with three‐dimensional, elastic‐plastic, finite‐element analyses to study constraint effects, crack tunnelling, and the fracture process . The constant‐CTOA criterion (from crack initiation to fracture) has been successfully applied to numerous structural applications, such as stiffened panels with multiple‐site damage (MSD) crack configurations, buckling behaviour of thin‐sheet materials, aircraft fuselages, and pipeline materials .…”
Section: Introductionmentioning
confidence: 99%
“…Later, the nonconstant CTOA values were traced to inappropriate state‐of‐stress (or constraint) assumptions in the crack‐front region and severe crack tunnelling in thin‐sheet materials . More recently, the CTOA fracture criterion has been used with three‐dimensional, elastic‐plastic, finite‐element analyses to study constraint effects, crack tunnelling, and the fracture process . The constant‐CTOA criterion (from crack initiation to fracture) has been successfully applied to numerous structural applications, such as stiffened panels with multiple‐site damage (MSD) crack configurations, buckling behaviour of thin‐sheet materials, aircraft fuselages, and pipeline materials .…”
Section: Introductionmentioning
confidence: 99%
“…This relationship analytically leads to higher CTOD values in the beginning of crack growth, and then progressively decreases to a nearly constant value for most of the materials that exhibit typical J-R curves. This is a common feature of the CTOA that can be seen from the literature data [6][7][8][9][10] (collectively reported by Newman et al [5]). Since it is well known that the J-R curve is specimen configuration dependent, it can be concluded that the CTOD may strongly depend on crack tip constraint.…”
Section: Discussionmentioning
confidence: 71%
“…Since CTOD and CTOA are equivalent, where appropriate, the term CTOD is understood to refer also to CTOA throughout the paper, unless it is specifically pointed out A comprehensive review of the work on CTOD can be found in Newman, et al [5]. The majority of the test data (e.g., aluminum alloys and A533B) and the numerical analyses (e.g., [1,[6][7][8][9][10][11][12][13][14][15][16][17][18][19]) seem to indicate that the values of CTOD are initially high, but progressively decrease to a nearly constant value after several millimeters of crack growth. It has been shown by several investigators (e.g., [9][10][11]15,[20][21][22][23]) that, based on three-dimensional (3D) and two-dimensional (2D) finite element analyses, a constant CTOD fracture criterion may be capable of predicting the experimental data (e.g., load versus crack extension curves).…”
Section: Introductionmentioning
confidence: 99%
“…Later, the non-constant CTOA values were traced to inappropriate state-of-stress (or constraint) assumptions in the crack-front region and severe crack tunneling in thin-sheet materials [20,25]. In the past two decades, the CTOA fracture criterion has been used with two-and three-dimensional, elastic-plastic, finite-element analyses to study constraint effects, crack tunneling, and the fracture process [26,27]. The constant CTOA criterion (from crack initiation to fracture) has been successfully applied to numerous structural applications, such as stiffened panels with multiple-site damage (MSD) crack configurations [28], buckling behavior of thin-sheet materials [29], an aircraft fuselage [30] and pipeline materials [31].…”
Section: Critical Crack-tip-opening-angle Fracture Criterionmentioning
confidence: 99%